ANTISEMITISM: A PSYCHOANALYTICAL READING OF CHAIM POTOK’S THE CHOSEN (International Journal of Food and Nutritional Sciences, 2022)
Antisemitism is a form of racism manifested in multiple ways. This prejudice or hostility is experienced by the Jewish people for centuries. The expressions ranging from hatred, discrimination towards the Jewish community can be witnessed in the works of the American Jewish writer Chaim Potok. The term anti-Semitism was first coined by the German agitator Wilhelm Marr in 1879. He designated the anti-Jewish campaigns under way in the Central Europe during that time. Potok’s characters do not become fully assimilated into American culture but maintain their own culture and try to balance their religious interests with their secular ones. The prejudice between the Orthodox Jews and the secular Jews and people outside their community is portrayed effectively in Chaim Potok’s The Chosen. This paper attempts to trace the problem of antisemitism in the novel.